Magnetic-based detection of muscular contraction for controlling hand prosthesis - Prakash A.; Sharma N.; Katiyar A.K.; Dubey S.K.; Sharma S. (My University, 2025)
Muscle contraction information from the residual upper-limb of an amputee can generate intention-based control to prosthetic devices. There are several approaches such as electromyography (EMG), force myography (FMG), and mechanomyography (MMG) that can directly or indirectly measure muscular contractions. However, these techniques suffer from the problems like ambient noise, motion artifacts, inappropriate contact with the skin, inaccurate output, and high cost of measurement. In this work, a novel magnetic-based Hall myography (HMG) technique is introduced that can precisely measure the muscular contractions from the subject's upper-limb. The sensor setup consists of a magnetic coupler and Hall element assembly separated by a mechanical spring. Any contraction from the muscle produces gradual movement of the magnet towards the hall element. This change in displacement is sensed by the hall element and is then translated to a 0–5 V linear output using appropriate preprocessing hardware and software. The sensor performance was evaluated in terms of sensitivity, repeatability, hysteresis, and frequency response. In detecting muscle contractions from the forearm of subjects, the sensor showed highly correlated output (r > 0.94, p-value<0.0001) with the EMG sensor. Moreover, the sensor showed better signal stability and similar dynamic behavior as compared to the EMG sensor. Further, the utility of the sensor was tested for controlling hand prosthesis. Subjects wearing the sensor were able to control the flexion of prosthetic hand fingers proportionally according to their intensity of muscle contraction. With several advantages, Hall myography can replace the EMG technique for prosthesis control application. © 2022 Elsevier B.V.